Imperialism in the Financial Capital Era: Forgotten Contributions from Marxist Dependency Theory - Nunes, Debora Machado (Review of Radical Political Economics, 2024)
This article argues that the contributions of Marxist Dependency Theory (MDT) can provide theoretical insights for the analysis of financialized capitalism dynamics, contribute to the debate about the rise of a globalized working class, and help guide a transformative praxis in the periphery, therefore being relevant for the debate of contemporary imperialism. I discuss which traditions of dependency theories were most featured in economics literature and why I believe that MDT is marginalized and misinterpreted, focusing on the historical and political aspects of that process. Next, I debate some contributions of contemporary imperialism theory, and conclude that MDT has the potential to advance some of its core concepts and formulate a powerful synthesis.JEL Classification: B51, F54
Keywords: Dependency Theory; Financialized Capitalism; Imperialism; Marxist Dependency Theory; Latin America